ARCHIVAL MANAGEMENT ANALYSIS AT THE PISANGAN BARU URBAN VILLAGE OFFICE - Sella Apriyani; Tasya Nurwindariyanto; Amanda Rivani (POLITEKNIK LP3I JAKARTA, 2026)
The Pisangan Baru Urban Village office still faces obstacles in managing its dynamic archives, such as annual changes to letter classification codes, limited storage capacity, and the absence of a formal archive-borrowing procedure. This study aims to analyse the process off managing incoming and outgoing correspondence, identify the constraints encountered, and formulate appropriate solutions. The method used is qualitative research with a descriptive approach through direct observation and in-depth interviews with the Secretary of the Pisangan Baru Urban Village Office as the key informant. The results show that the management of incoming and outgoing letters has been carried out in a structured manner through a single archivist, supported by a manual numbering system and digital applications such as e-Office, Arjuna, and Siska. The main constraints found include inconsistent letter classification codes, a fully occupied archive storage room, and an informal file-borrowing mechanism. As solutions, the village office actively coordinates with sub-district archivists, uses air-conditioned room as temporary storage, and plans the procurement of a dedicated storage room and archival aquipment. This study concludes that optimizing are necessary to support more efficient archival digitization at the Pisangan Baru Urban Village Office.